The use and reliability of SymNose for quantitative measurement of the nose and lip in unilateral cleft lip and palate patients. Issue 10 (October 2016) - Mosmuller, David; Tan, Robin; Mulder, Frans; Bachour, Yara; de Vet, Henrica; Don Griot, Peter
Abstract: Introduction: It is essential to have a reliable assessment method in order to compare the results of cleft lip and palate surgery. In this study the computer-based program SymNose, a method for quantitative assessment of the nose and lip, will be assessed on usability and reliability. Methods: The symmetry of the nose and lip was measured twice in 50 six-year-old complete and incomplete unilateral cleft lip and palate patients by four observers. For the frontal view the asymmetry level of the nose and upper lip were evaluated and for the basal view the asymmetry level of the nose and nostrils were evaluated. Results: A mean inter-observer reliability when tracing each image once or twice was 0.70 and 0.75, respectively. Tracing the photographs with 2 observers and 4 observers gave a mean inter-observer score of 0.86 and 0.92, respectively. The mean intra-observer reliability varied between 0.80 and 0.84. Conclusions: SymNose is a practical and reliable tool for the retrospective assessment of large caseloads of 2D photographs of cleft patients for research purposes. Moderate to high single inter-observer reliability was found. For future research with SymNose reliable outcomes can be achieved by using the average outcomes of single tracings of two observers.